2020
DOI: 10.1177/1534735420908341
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Interventions in Recurrent Ovarian Cancer: A Mixed-Methods Feasibility Study

Abstract: A recurrence of cancer is a traumatic and stressful experience, and a number of approaches have been proposed to manage or treat the associated psychological distress. Meditative techniques such as mindfulness may be able to improve an individual’s ability to cope with stressful life events such as cancer diagnosis or treatment. This single-arm mixed-methods study primarily aimed to determine the feasibility of using a mindfulness-based intervention in managing psychosocial distress in recurrent ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(64 citation statements)
references
References 39 publications
2
59
0
2
Order By: Relevance
“…The SCL-90 scale has some scientificity and practicability in assessing the psychiatric symptoms or psychological status of the subjects from emotional, conscious, thinking, and behavioral aspects [ 46 ]. The results of SCL-90 scores in patients and controls were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The SCL-90 scale has some scientificity and practicability in assessing the psychiatric symptoms or psychological status of the subjects from emotional, conscious, thinking, and behavioral aspects [ 46 ]. The results of SCL-90 scores in patients and controls were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that ovarian cancer patients need to have a light diet and a reasonable diet control, and poor dietary habits will adversely affect the treatment of advanced ovarian cancer patients. Therefore, it is of great significance to improve the quality of life and prolong the survival time of ovarian cancer patients to pay attention to the changes of their psychological state and control their dietary habits while providing effective treatment for ovarian cancer patients [ 20 ]. Nursing should be based on the patient's condition and actual conditions, implement high-quality psychological interventions and high-quality diet care, and provide guidance on TCM, which reflects the comprehensiveness and individualization of the treatment process [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies examined the effectiveness of a written emotional disclosure intervention. 22,31 While the intervention parameters were similar (non-face-to-face intervention of 15 min duration), the results differed. The study by Arden-Close et al 22 reported no effect on QOL, intrusive thoughts, or perceived stress following the intervention compared with the control condition.…”
Section: Effectiveness Of Psychosocial Interventionsmentioning
confidence: 95%
“…22,31 While the intervention parameters were similar (non-face-to-face intervention of 15 min duration), the results differed. The study by Arden-Close et al 22 reported no effect on QOL, intrusive thoughts, or perceived stress following the intervention compared with the control condition. This contrasted with the results from Popovska 31 who reported an increased emotional burden post writing session despite improvements in overall emotional well-being at 1-month follow-up.…”
Section: Effectiveness Of Psychosocial Interventionsmentioning
confidence: 95%
See 1 more Smart Citation